2013
DOI: 10.1016/j.appet.2013.01.025
|View full text |Cite
|
Sign up to set email alerts
|

Within- and between-session variety effects in a food-seeking habituation paradigm

Abstract: Appetitive behavior is stronger when organisms are given a variety of foods than when they are repeatedly given the same food (the variety effect). Two experiments examined the variety effect in an operant food-seeking task. In both experiments, rats received a 45-mg food pellet for every 4th lever press over a series of daily 30-min sessions. The rats responded at a high rate early in the session, but the rate declined systematically over time within the session. In Experiment 1, alternating unpredictably bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
37
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 20 publications
(40 citation statements)
references
References 19 publications
2
37
1
Order By: Relevance
“…In this sense, variety can enhance responding between-sessions by virtue of a mechanism that is different from habituation. It is worth noting, however, that Bouton et al (2013) also observed less responding to the grain pellet in the alternating group than in a group that received grain pellets consistently. Thus, the two pellets produced both positive and negative incentive contrast, and the average level of responding across sucrose and grain sessions was not different from that of the control animals.…”
Section: Introductionmentioning
confidence: 85%
See 4 more Smart Citations
“…In this sense, variety can enhance responding between-sessions by virtue of a mechanism that is different from habituation. It is worth noting, however, that Bouton et al (2013) also observed less responding to the grain pellet in the alternating group than in a group that received grain pellets consistently. Thus, the two pellets produced both positive and negative incentive contrast, and the average level of responding across sucrose and grain sessions was not different from that of the control animals.…”
Section: Introductionmentioning
confidence: 85%
“…Interestingly, Bouton et al (2013, Experiment 2) also isolated a second “variety effect” that was not linked to within-session habituation. When rats were given alternating sessions that contained grain or sucrose pellet reinforcers consistently, the amount of responding for sucrose during sucrose sessions exceeded that observed in a control group that only earned sucrose pellets in every session.…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations